Collision‐induced dissociation of synthetic polymers containing hydride groups: the case of poly(methylhydrosiloxane) homopolymers and poly(methylhydrosiloxane)‐co‐(dimethylsiloxane) copolymers. (21st November 2012) - Fouquet, Thierry; Chendo, Christophe; Toniazzo, Valérie; Ruch, David; Charles, Laurence
<x xml:space="preserve">Abstract</x> RATIONALE When substituting one methyl moiety by a hydrogen atom in each end‐group of a trimethylsilyl‐terminated poly(dimethylsiloxane) (PDMS), dissociation reactions of oligomers adducted with ammonium were observed to proceed at a much higher rate, evidencing the high reactivity of hydride groups. Polymeric molecules containing methylhydrosiloxane (MHS) units could thus be expected to exhibit a different tandem mass spectrometric (MS/MS) behavior from PDMS. METHODS Trimethylsilyl‐terminated PMHS and trimethylsilyl‐terminated poly(MHS)‐co‐(DMS) were electrosprayed in the gas phase either as ammonium adducts or lithium adducts. Product ions generated upon collision‐induced dissociation (CID) were accurately mass measured in an orthogonal acceleration time‐of‐flight mass analyzer. RESULTS In contrast to PDMS adducted with lithium, useful structural features could be obtained from product ions generated upon CID of lithium adducts of PMHS. The presence of multiple hydride groups in PMHS induced numerous rearrangements when activating ammonium adducts of these oligomers. MS/MS reactions observed for cationic adducts of MHS‐DMS co‐oligomers were clearly a combination of major dissociation routes established for the corresponding homopolymers. However, the concerted loss of H2 and ammonia typically observed from ammonium adducts of PMHS was always shown to generate a quite abundant product ion even from co‐oligomers enriched with DMS units. CONCLUSIONS The high reactivity of hydride moieties, previously evidenced when these groups were at the end of PDMS chains, is also at work in PMHS, where each monomer contains a Si‐H function. The presence of these hydride groups would increase the nucleophilic character of the oxygen atoms, favoring a tight bonding of lithium, and hence allowing in‐chain cleavages to occur. In PMHS ammonium adducts, the particular reactivity of hydride moieties was illustrated by multiple hydride transfers but also by a dehydrogenation reaction systematically observed to proceed, together with the loss of ammonia, from all precursor ions. This latter reaction remained a very competitive process even from MHS/DMS co‐oligomers with a low relative number of MHS units. Copyright © 2012 John Wiley & Sons, Ltd.